Investigating EFL Students’ Perception nn English Basic Vocabulary Teaching Through Pictures for the First Year Students of SMA Datuk Ribandang Makassar - Abdollah Abdollah; Hariratul Jannah; Hardiyansyah Hardiyansyah (Tamaddun Life, 2020)
This study aims to find out the EFL students’ perception in regards to basic English vocabulary teaching through pictures. This study was conducted in a senior high school situated in Makassar, South Sulawesi, called SMA Datuk Ribandang Makassar. This study is about students’ teaching English basic vocabulary through pictures. A quantitative method were use to how the effects of basic vocabulary teaching through pictures are. A qualitative study determine students’ perception in teaching vocabulary through pictures. Based on the findings and discussion the previous chapter, the researcher concludes that the effect vocabulary through pictures by the students’ in Learning English showed from pre-test and post Mean score of 27 students pre-test was 48,74 (with standart deviation 14,482 and standard errror mean was 2,5787) and the students’ post-test mean score was 77,70 (with standart deviation 10,498 and standard errror mean was 2,020). Furthermore, Students’ perception of English basic vocabulary through pictures for the firsy years students of SMA Datuk Ribandang Makassar gives the positive perception that exactly students’ perception of the teacher method in teaching English.